Geographic market intelligence as a competitive advantage - Guarda, Teresa (2019)
Advances in information and communication technologies are providing more and more alternative ways to accessing information and storage data, as well a greater accessibility to multiple devices, transforming Internet of Things into a giant digital ecosystem, revolutionizing the business models also in the area of marketing. According to Gartner's, IoT will have a major impact on the economy, facilitating and create opportunities to new business models. This article covers a range of techniques, tools and a model that address geographic market intelligence, examining how the benefits of these can contribute to greater effectiveness in marketing campaigns and the maintenance or acquisition of competitive advantage.